2018
DOI: 10.1097/qai.0000000000001629
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Higher ART Adherence Is Associated With Lower Systemic Inflammation in Treatment-Naive Ugandans Who Achieve Virologic Suppression

Abstract: Higher ART adherence was associated with lower levels of biomarkers of inflammation, immune activation, and coagulopathy among Ugandans living with HIV who achieved viral suppression shortly after ART initiation. This suggests that ART adherence could have biological consequences beyond viral suppression. Whether ART adherence optimization in virologically suppressed individuals could reduce residual inflammation remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…ARV adherence was determined through self-report, using the following question: ‘In the past month, how many days did you miss a dose of your ARVs?’ One month recall of ARV adherence is associated with objective measures of adherence (see the ‘Limitations’ section) (Buscher et al ., 2011 ). While we are aware that with modern ARV treatment, viral suppression can be achieved with only 80–84% adherence (Viswanathan et al ., 2015 ), in light of emerging data showing that even in the setting of viral suppression, suboptimal (<100%) adherence correlates with significant clinical outcomes, including higher inflammation and residual viral replication (Li et al ., 2014 ; Castillo-Mancilla et al ., 2018 a , b ), we opted for a stringent definition of adherence, using a bivariate model assessing adherence over the past month in which 1 = no missed doses and 0 = doses missed.…”
Section: Methodsmentioning
confidence: 99%
“…ARV adherence was determined through self-report, using the following question: ‘In the past month, how many days did you miss a dose of your ARVs?’ One month recall of ARV adherence is associated with objective measures of adherence (see the ‘Limitations’ section) (Buscher et al ., 2011 ). While we are aware that with modern ARV treatment, viral suppression can be achieved with only 80–84% adherence (Viswanathan et al ., 2015 ), in light of emerging data showing that even in the setting of viral suppression, suboptimal (<100%) adherence correlates with significant clinical outcomes, including higher inflammation and residual viral replication (Li et al ., 2014 ; Castillo-Mancilla et al ., 2018 a , b ), we opted for a stringent definition of adherence, using a bivariate model assessing adherence over the past month in which 1 = no missed doses and 0 = doses missed.…”
Section: Methodsmentioning
confidence: 99%
“…Non-virologic parameters associated with excess risk of mortality, such as increased bacterial translocation or inflammation (9,10), are often assumed to be a consequence of the immune damage elicited by acute HIV infection, but no longer affected by HIV replication in individuals on ART. However, even during HIV RNA suppression in PWH, a lower ART adherence to 3-drug regimens (3DR) is associated with increased levels of inflammatory biomarkers, suggesting that a decrease in drug concentrations results in virologic phenomena in tissues, not detected in plasma, that elicit immune activation (11)(12)(13). Mounting evidence generated in SIV-infected macaques, HIVinfected humanized mice, and humans indicates that antiretrovirals are distributed very heterogeneously within lymphoid tissues (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…While long-term ART, particularly with use of specific antiretroviral drugs, has been associated with some metabolic complications, including hyperlipidemia and myocardial infarction [ 12 , 13 ], ART also has beneficial effects in decreasing inflammatory and coagulation biomarkers. Studies have shown declines in D-dimer levels following treatment initiation, and have further demonstrated that delayed ART, poor treatment adherence and interruption of ART may contribute to elevated coagulation markers and increased risk of death [ 4 , 14 16 ]. Nonetheless, compared to HIV-negative persons, higher D-dimer levels have been shown to persist even in PLHIV who maintain viral suppression on long-term ART [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%